Ultrastructure of cervical intraepithelial neoplasia - Recavarren, Sixto (2015)
In recent years, the use of new methods and morphological techniques in the study of epithelial cervical neoplasia has allowed reveal structural alterations besides mean changes have hitherto little known, served for a better understanding of the behavior biiológica these neoplasms.